About the sectoral centres for prediction of scientific and technical development - P. . Iosifov; A. . Pervanyuk; M. . Siluyanova (Moscow Polytechnic University, 2022)
The article describes the methodological principles of forming the network including the sectoral prediction centres developing the priority direction "Transport and Cosmic Systems"on the basis of the leading Russian universities. The classification of the main goals of the prediction centres' activities is given, and the key consumers are defined.